1993
DOI: 10.1021/la00029a037
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer in self-assembled monolayers of N-methyl-N'-carboxyalkyl-4,4'-bipyridinium linked to gold electrodes

Abstract: Electron transfer processes in monolayer assemblies formed by covalent linkage of JV-methyl-JV'carboxyalkyl-4,4'-bipyridinium (1) to cystamine, chemisorbed onto gold electrodes, are examined. The resulting monolayer exhibits nonordered structure being reflected by a similar rate constant to the bipyridinium redox sites, that is independent of the bridging alkyl chain length, ket = 550 a-1. The nonordered structure is also confirmed by the low electron transfer coefficients aa and ac, corresponding to 0.25 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…In both instances, the sulfur‐containing functional group ensures the adsorption of these compounds on the surface of a gold electrode and the bipyridinium dication imposes electroactive character on the resulting films. A different approach to similar monolayers is based, instead, on the use of bipyridinium compounds with pendant carboxylic acids 42. For example, a gold electrode can be coated with a monolayer of cystamine.…”
Section: Self‐assembling Bipyridinium Monolayersmentioning
confidence: 99%
“…In both instances, the sulfur‐containing functional group ensures the adsorption of these compounds on the surface of a gold electrode and the bipyridinium dication imposes electroactive character on the resulting films. A different approach to similar monolayers is based, instead, on the use of bipyridinium compounds with pendant carboxylic acids 42. For example, a gold electrode can be coated with a monolayer of cystamine.…”
Section: Self‐assembling Bipyridinium Monolayersmentioning
confidence: 99%
“…The electron transfer for SAM of various compounds with redox moieties on a gold electrode has been studied so that the rate constant is found to increase with decreasing the distance between the redox group and the electrode according to the Marcus theory [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The phospholipid-linked manganese porphyrins exhibited an enhanced electron transfer activity, depending upon the length of the spacer methylene group (C n ) and also the structure of manganese porphyrins. Alternatively, a large number of chemists have identified that electroactive species such as porphyrins, myoglobin, flavins, viologens, ferrocenes and quinones can be immobilized on electrode surfaces [23][24][25][26][27][28][29]. However, there has been little study of electron transfer between quinones or porphyrins complexes on an electrode modified with lipid bilayers 0927 [4,30,31].…”
Section: Introductionmentioning
confidence: 99%